Engineering anisotropic human stem cell-derived three-dimensional cardiac tissue on-a-chip. (October 2020) - Veldhuizen, Jaimeson; Cutts, Joshua; Brafman, David A.; Migrino, Raymond Q.; Nikkhah, Mehdi
Abstract: Despite significant efforts in the study of cardiovascular diseases (CVDs), they persist as the leading cause of mortality worldwide. Considerable research into human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) has highlighted their immense potential in the development of in vitro human cardiac tissues for broad mechanistic, therapeutic, and patient-specific disease modeling studies in the pursuit of CVD research. However, the relatively immature state of hPSC-CMs remains an obstacle in enhancing clinical relevance ofengineered cardiac tissue models. In this study, we describe development of a microfluidic platform for 3D modeling of cardiac tissues, derived from both rat cells and hPSC-CMs, to better recapitulate the native myocardium through co-culture with interstitial cells (specifically cardiac fibroblasts), biomimetic collagen hydrogel encapsulation, and induction of highly anisotropic tissue architecture. The presented platform is precisely engineered through incorporation of surface topography in the form of staggered microposts to enable long-term culture and maturation of cardiac cells, resulting in formation of physiologically relevant cardiac tissues with anisotropy that mimics native myocardium. After two weeks of culture, hPSC-derived cardiac tissues exhibited well-defined sarcomeric striations, highly synchronous contractions, and upregulation of several maturation genes, including HCN1, KCNQ1, CAV1.2, CAV3.1, PLN, and RYR2. These findings demonstrate the ability of the proposed engineered platform to mature animal- as well as human stem cell-derived cardiac tissues over an extended period of culture, providing a novel microfluidic chip with the capability for cardiac disease modeling and therapeutic testing.